Methods Applied in Developing Students' English Speaking Confidence at MA Al Ma'arif NU Lombok - Cao Huaixuan; Heri Hadi Saputra; Sudirman (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study scrutinized teachers' strategies for developing students' speaking confidence. The qualitative approach was adopted using observation and interviews as data collection methods. Four English teachers with a myriad of experiences in coping with students' problems with speaking confidence were invited as samples. The analysis of data procedures involved Kawulich's (2004) work, including Narrative, Coding, Interpretation, Confirmation, and Presentation. The findings revealed that the students had low confidence in speaking due to being Afraid of Speaking, Feeling Inferior, and Being Shy. Teachers developed strategies to cope with problems, including guiding the students when speaking, conducting peer tutoring, habituating students to speak, and giving games to motivate them to learn. Based on the data, some improvements were achieved after the strategies: teachers as guides followed by speaking as habits improved students' speaking confidence; Peer Tutors and Teachers as Guides boost students' understanding; Peer Tutors and Games promote more enthusiasm for students. This study recommends that the principals facilitate teachers' autonomy in teaching, such as conducting programs compatible with students' learning needs by providing collaborative learning opportunities and involving fun learning activities to get students' enthusiasm, which will generate their motivation and confidence